Subsurface Lateral Flow in Texture-Contrast (Duplex) Soils and Catchments with Shallow Bedrock. (8th February 2012) - Hardie, Marcus A.; Doyle, Richard B.; Cotching, William E.; Lisson, Shaun
Abstract : Development-perched watertables and subsurface lateral flows in texture-contrast soils (duplex) are commonly believed to occur as a consequence of the hydraulic discontinuity between the A and B soil horizons. However, in catchments containing shallow bedrock, subsurface lateral flows result from a combination of preferential flow from the soil surface to the soil—bedrock interface, undulations in the bedrock topography, lateral flow through macropore networks at the soil—bedrock interface, and the influence of antecedent soil moisture on macropore connectivity. Review of literature indicates that some of these processes may also be involved in the development of subsurface lateral flow in texture contrast soils. However, the extent to which these mechanisms can be applied to texture contrast soils requires further field studies. Improved process understanding is required for modelling subsurface lateral flows in order to improve the management of waterlogging, drainage, salinity, and offsite agrochemicals movement.